Global energy consumption and importance of renewable resources - Кондыбаева, С.; Кабылкайраткызы, Р. (Journal of Economic Research & Business Administration, 2017)
Energy is inevitable for human life and a secure and accessible supply of energy is crucial for the sustainability of modern societies. Achieving solutions to environmental problems that we face today requires long-term potential actions for sustainable development. Economic growth, along with accompanying structural changes, strongly influences world energy consumption. As countries develop and living standards improve, energy demand grows rapidly. Increased demand for appliances and transportation equipment, and growing capacity to produce goods and services for both domestic and foreign markets, also lead to higher energy consumption. From this perspective, renewable energy resources are in all likelihood the one of the most efficient and effective solutions. That is why there is an intimate connection between renewable energy and sustainable development. This article presents current energy resources data and human activity on it. As energy consumption and economic growth of world is directly depends on each other, here the issue about efficiency of energy saving. Active and passive measures which can be taken by us, can solve some issues relating to energy consumption problems.